Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/jpe/rtaa018
|View full text |Cite
|
Sign up to set email alerts
|

Importance of starting points in heterogeneous environments: interactions between two clonal plants with contrasting spatial architectures

Abstract: Abstract Aims Plants can benefit from heterogeneous environments via disproportionately increasing resource harvesting in resource-rich patches. Their initial growing positions with respect to resource patches may thus have important influences on their performance and relative competitive ability. Such impacts may differ between species with contrasting spatial architectures. However, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In contrast, clonal wetland plants that exhibit the guerrilla growth form have a flexible distribution of ramets connected by many and/or long spacers [24,39]. Phalanx clonal plants thrive in stable and homogeneous habitats, while guerrilla clonal plants grow in disturbed and heterogeneous habitats [41,28,40]. For example, soil nutrient heterogeneity significantly increased the relative yield of the guerrilla clonal plant Bolboschoenus planiculmis and decreased that of the phalanx clonal plant Carex neurocarpa [39].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, clonal wetland plants that exhibit the guerrilla growth form have a flexible distribution of ramets connected by many and/or long spacers [24,39]. Phalanx clonal plants thrive in stable and homogeneous habitats, while guerrilla clonal plants grow in disturbed and heterogeneous habitats [41,28,40]. For example, soil nutrient heterogeneity significantly increased the relative yield of the guerrilla clonal plant Bolboschoenus planiculmis and decreased that of the phalanx clonal plant Carex neurocarpa [39].…”
Section: Introductionmentioning
confidence: 99%
“…When growing in spatially heterogeneous environments consisting of favorable and unfavorable patches, many plants are able to allocate more roots and/or shoots in favorable patches and less in unfavorable patches ( Hutchings et al., 2003 ; Dong et al., 2015 ; Liu et al., 2020 ), and such a foraging response may help them take up more resources and increase their growth ( Rajaniemi and Reynolds, 2004 ; Questad and Foster, 2008 ; Xue et al., 2020 ). We also found that the plant communities showed patch-level foraging responses in the environments with the spatially heterogeneous distribution of soil microplastics.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have assessed the ecological impacts of soil heterogeneity in the horizontal distribution of factors other than microplastics, including nutrients ( Tsunoda et al., 2014 ; Xue et al., 2020 ; Adomako et al., 2021a ; Gao et al., 2021 ), water ( You et al., 2016 ; Wang et al., 2017 ), heavy metals ( Roiloa and Retuerto, 2012 ; Xu and Zhou, 2017 ) and particle size of the soil ( Baer et al., 2005 ; Huang et al., 2013 ; Xue et al., 2016 ). These studies have shown that soil heterogeneity in the distribution of such factors can affect growth, morphology and physiology of individual plants ( Zhou et al., 2012 ; Tsunoda et al., 2014 ; Adomako et al., 2021b ; Si et al., 2021 ), influence dynamics of plant populations ( Hutchings et al., 2003 ; Baer et al., 2020 ), modify intraspecific and interspecific plant-plant interactions ( Liang et al., 2020 ; Xue et al., 2021 ; Hu et al., 2022 ), and change plant community structure and ecosystem function ( Wijesinghe et al., 2005 ; Yao et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The environment that plants face is commonly not spatially uniform, but heterogeneous ( Hutchings and Wijesinghe, 1997 ; Ikegami et al., 2008 ; Keser et al., 2014 ). Spatial heterogeneity in resource supply makes resource capture more costly and challenging for sessile organisms ( Magyar et al., 2007 ; Ikegami et al., 2008 ; Wang et al., 2017 ; Li et al., 2018 ; Xue et al., 2020 ). However, clonal growth allows many clonal plants to produce interconnected ramets that are situated in patches (microsites) of different resource availability ( Price and Marshall, 1999 ; Roiloa and Retuerto, 2006 ; Ikegami et al., 2008 ; You et al., 2016 ; Xue et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial heterogeneity in resource supply makes resource capture more costly and challenging for sessile organisms ( Magyar et al., 2007 ; Ikegami et al., 2008 ; Wang et al., 2017 ; Li et al., 2018 ; Xue et al., 2020 ). However, clonal growth allows many clonal plants to produce interconnected ramets that are situated in patches (microsites) of different resource availability ( Price and Marshall, 1999 ; Roiloa and Retuerto, 2006 ; Ikegami et al., 2008 ; You et al., 2016 ; Xue et al., 2020 ). Via clonal integration, interconnected ramets can transfer and share resources so that ramets growing in low-quality resource patches can get support from ramets growing in high-quality resource patches ( Roiloa et al., 2010 ; Song et al., 2013 ; Wang et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%